Institutional development of voluntary health insurance market in Ukraine - Слободянюк, Ольга Василівна; Слободянюк, О. В.; Слободянюк, Ольга Васильевна; Slobodianiuk, Olha V.; Slobodyanyuk, Olga (Institute of Society Transformation, 2016)
Introduction. Many reforms are taking place in Ukraine within the framework of the European integration. Modernisation of the health care system is one of them. In Europe, medical insurance possesses are one of the most significant elements of the insurance market along with car and property insurance. Notwithstanding this fact, the development of the Ukrainian voluntary health insurance system is obstructed by several major objective and subjective factors. Purpose and Results. This article examines classification of the voluntary health insurance system, demonstrates trends in the dynamics of voluntary health insurance development, shows peculiarities of quantitative and qualitative changes in its constituents and identifies problems and prospects of its development in Ukraine. Such methods of research, as system approach, analysis and synthesis, dynamics and structure valuation, and market segmentation have been used. The authors of this article have generalised the classification of the voluntary health insurance and calculated shares of insurance premiums for voluntary health insurance contracts and the level of insurance payouts. The article determines the dynamics of the volume and level of insurance payments on voluntary medical insurance in Ukraine in 2010-2015; as well as quantitative and qualitative characteristics of the institutional development of the voluntary medical insurance in the country. Besides, the factors that have a negative impact on the development of this part of the insurance market have been defined.

У статті доведено важливість послуг добровільного медичного страхування як інструменту захисту соціально-економічних інтересів індивідуальних і корпоративних клієнтів. Уточнено класифікацію добровільного медичного страхування за видами, суб’єктами, умовами договорів. На основі кількісних оцінок проаналізовано значущість добровільного медичного страхування як сегмента страхового ринку. Визначено закономірності динаміки чистих страхових премій і частки страхових виплат на ньому, а також перспективи розвитку вказаного сегмента, які пов’язані з формуванням конкурентного середовища та діяльністю асистанських компаній.
Slobodyanyuk O. Institutional development of voluntary health insurance market in Ukraine / O. Slobodyanyuk // Economic Annals-ХХІ. - Vol. 160. - Issue: 7-8. - Institute of Society Transformation, 2016. - Р. 130-133
Keywords: Institutional Development; Health Insurance; Market; Voluntary Health Insurance; інституціональний розвиток; медичне страхування; ринок; Research Subject Categories::SOCIAL SCIENCES::Business and economics::Economics